O3.1. CLUSTER ANALYSIS FINDS THREE CLINICALLY-RELEVANT SUBGROUPS OF TRAIT EMOTIONAL EXPERIENCE IN SCHIZOPHRENIA OUTPATIENTS. (18th May 2020) - Cowan, Henry; Mittal, Vijay; Allen, Daniel; Gold, James; Strauss, Gregory
Abstract: Background: Previous research shows that trait emotion is more affected than state emotion in schizophrenia. This literature is also somewhat inconsistent, particularly in terms of specific links between affective traits and clinical symptoms. The current study examined whether subgroups of trait emotional experience predict symptom presentation and functional outcome in schizophrenia. Methods: In this cross-sectional observational study, 192 outpatients diagnosed with schizophrenia or schizoaffective disorder (SZ) and 149 matched healthy controls completed the trait version of the Positive and Negative Affect Scale and symptom and functional outcome assessments. Cluster and discriminant function analyses identified distinct profiles of trait affect, which were then compared on clinical and functional variables. Results: Three SZ clusters reflected normative affect (n = 80, 42%), low trait positive affect (PA; n = 54, 28%), and high trait negative affect (NA; n = 58, 30%), compared to controls. Symptom profiles differentiated the three subgroups. Compared to the Normative Affect cluster, the Low PA cluster had more severe negative symptoms; the High NA cluster had more severe positive symptoms, disorganization, anxiety, and depression; and both the Low PA and High NA cluster had poorer overall functioning. Diagnostic and medication status also differentiated the three subgroups. The Low PA subgroup was most likely to be prescribed 1st-generation antipsychotics, while the High NA subgroup was most likely to be diagnosed with schizoaffective disorder. Discussion: Distinct subgroups with unique trait affect profiles can be identified within the broader diagnosis of schizophrenia. These subgroups show meaningful clinical differences in presentation, with theoretical and clinical implications.